Endometrial biopsy in women with abnormal uterine bleeding: inadequate and unassessable categorisation is not clinically relevant. Issue 8 (23rd May 2014) - Ewies, Ayman A A; Shaaban, Kadry A A; Merard, Reena; Zanetto, Ulises
Abstract : Aims: Inadequate endometrial biopsy comprises a dilemma for gynaecologists and histopathologists alike. This study was conducted to assess the clinical merit of classifying scant endometrial biopsy into inadequate and unassessable using McCluggage criteria. Methods: We retrospectively classified 268 endometrial biopsies, initially reported as inadequate, into inadequate (n=74) and unassessable (n=174) using McCluggage criteria after excluding 20 cases; all taken from patients aged ≥50 years with abnormal uterine bleeding attending Sandwell and West Birmingham Hospitals, UK from 1 January 2007 until 30 September 2012. The electronic clinical records were reviewed to find out the consequent clinical decisions and final outcomes. The follow-up period was 15 months after including the last patient. Results: The median age was 57 years (range: 50–97), and the median number of visits to hospital till the diagnosis was achieved was 2 (range: 1–4). The final diagnosis of endometrial hyperplasia or cancer was reported in 9 cases; 5 (7.1%) with an initial finding of inadequate and 4 with unassessable (2.4%); the difference was statistically insignificant (p=0.13). More patients in the inadequate category (82.4%) underwent further investigations when compared with the unassessable category (68.4%); the difference was statistically significant (p=0.029). There was no statistically significant difference in the inadequate to unassessable ratio when the endometrial thickness was ≥5 mm or <5 mm within the Pipelle group (p=0.46) or the curettage group (p=0.34). Conclusions: Our findings suggest that categorising scant endometrial specimens into inadequate or unassessable has no clinical implications. The gynaecologist should interpret the histopathology report in the light of clinical scenario.